1993
DOI: 10.1121/1.406675
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and visual localization performance in a sequential discrimination task

Abstract: Four subjects were tested in a two-alternative, forced-choice, three down-one up adaptive paradigm in which two 200-ms signals were presented sequentially with a 200-ms interstimulus interval. The subject's task was to indicate whether the second stimulus was to the right or left of the first. Tests were conducted with 57 dB (A-weighted), 1.0-kHz high-pass noise, the minimum audible angle (MAA) task, and with lights emitting 620 nm at a luminance level of 200 mL, the minimum visible angle (MVA) task. Localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…This probably is due to a more refined capability for discriminating between adjacent sound sources centrally than in the periphery. On the basis of earlier studies in cats (Jenkins & Masterton, 1982), it was found that humans can discriminate adjacent sound sources directly in front of them when separated by only 2°_3°, whereas discrimination between peripheral sounds (e.g., at 40°azimuth) was markedly inferior (Perrott, Constantino, & Cisneros, 1993; see also Oldfield & Parker, 1984). Clearly, the sharpness of attentional allocation to a particular sound source among nearby competing sources depends in part on the ability to discriminate the location of the attended source from those of its neighbors.…”
Section: Time Course Analysismentioning
confidence: 98%
“…This probably is due to a more refined capability for discriminating between adjacent sound sources centrally than in the periphery. On the basis of earlier studies in cats (Jenkins & Masterton, 1982), it was found that humans can discriminate adjacent sound sources directly in front of them when separated by only 2°_3°, whereas discrimination between peripheral sounds (e.g., at 40°azimuth) was markedly inferior (Perrott, Constantino, & Cisneros, 1993; see also Oldfield & Parker, 1984). Clearly, the sharpness of attentional allocation to a particular sound source among nearby competing sources depends in part on the ability to discriminate the location of the attended source from those of its neighbors.…”
Section: Time Course Analysismentioning
confidence: 98%
“…Few studies have attempted to directly compare spatial acuity for auditory and visual stimuli throughout the visual field and focus instead on the spatial capture observed when spatially separated auditory-visual signals are presented (Howard and Templeton, 1966; Bertelson and Radeau, 1981). Two exceptions to this are Perrot et al (1993) and Charbonneau et al (2013). Both determined that both visual and auditory localisation judgments declined as stimuli move from central to peripheral space.…”
Section: Introductionmentioning
confidence: 99%
“…Both auditory (Mills, 1958; Makous and Middlebrooks, 1990; Charbonneau et al , 2013; Wood and Bizley, 2015; Carlile et al , 2016) and visual localisation acuity declines with eccentricity (Mateeff and Gourevich, 1984; Perrott et al , 1993; Charbonneau et al , 2013). Few studies have attempted to directly compare spatial acuity for auditory and visual stimuli throughout the visual field and focus instead on the spatial capture observed when spatially separated auditory-visual signals are presented (Howard and Templeton, 1966; Bertelson and Radeau, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…While auditory localization also decreases (Makous and Middlebrooks, 1990;Perrott and Saberi, 1990), spatial resolution degrades more slowly than vision (Perrott et ai, 1993). Perrott et al (1993) measured the minimum audible angles (MAA) and minimum visible angles (MVA) over a wide horizontal area (0°-80°) and found that the MAA was equal to or larger than the MVA for all regions beyond a 20°-periphery of the fovea. If the most likely location of an audio-visual target depends on uncertainties individually associated with auditory and visual cues, the dominant modality in localization must be changed by eccentricity.…”
Section: Introductionmentioning
confidence: 99%